Quantification of residual enrofloxacin and ciprofloxacin in feathers of broiler chickens by high-performance liquid chromatography-fluorescence after oral administration of the drugs - Griselda Haag; Gustavo H Marin; Jorge Errecalde (Wolters Kluwer Medknow Publications, 2016)
Enrofloxacin (ENR) and ciprofloxacin (CIP) are drugs used in poultry feeding. In general, feathers that are incorporated in the food chain as a protein source for animal feed, have residues of these drugs. In order to study the pharmacokinetic of ENR/CIP residues in feathers of broiler chickens, to calculate the waiting times for these drugs, before human consumption, we developed the present research. Feathers of broiler chickens were enriched with ENR/CIP. After adding acetone, the mix was agitated and centrifuged and supernatant evaporated under nitrogen. The dry residue was suspended in a tetrahydrofuran solution and the supernatant was injected into the chromatographic system for analysis. Animals showed high levels of ENR/CIP in their feathers after administration of 10 mg/kg enrofloxacin dissolved in drinking water for 5 days. Both compounds were detected in feathers during 9 days. The analytical method developed in this paper to determine ENR and CIP in feathers of broiler chicken showed good linearity, selectivity, accuracy and precision in the analysis conditions. This technique could have important applications in the studies on residues of ENR/CIP in feathers, since the effect of this component in animal diets has not been considered yet.